COMPARISON OF THE ACCURACY OF THE GCS AND FOUR SCALE ASSESSMENTS TO THE PROGNOSIS OF INTEGRATIVE REVIEW CONSCIOUSNESS DISORDER PATIENTS - Muhammad Ramli arsyad; Rosyidah Arafat; Elly LSjattar LSjattar (Indonesian Journal of Multidisciplinary Science, 2022)
The FOUR Scale is an awareness assessment score. Its theoretical benefit over pre-existing scores is the evaluation of brainstem reflexes and breathing patterns which allows a better assessment of patients with severe impairment of consciousness. The article search was carried out using the Four Data Bases. Inclusion criteria were: human, adult, prospective randomized controlled trial; prospective, cohort/control, case series, prospective, and retrospective studies. Inclusion and exclusion criteria were applied to each article to get the final article for review. Results in the adult population are presented here. Data were reported following the preferred reporting items for integrative review and meta-analysis guidelines. Initial search returned 103 citations. after screening the remaining 65 were for full-text review and 45 were excluded because they were based on review titles and abstracts and did not meet study design and population criteria. Patient categories included traumatic brain injury, intraventricular hemorrhage, intracerebral hemorrhage, subarachnoid hemorrhage, ischemic stroke, general neurology/ combined and neurosurgery, general critical illness/medicine, and patients in the emergency department. Until the remaining 20 studied. Twelve studies demonstrated good interobserver reliability of the FOUR Scale. Three studies demonstrated the prognostic value of the FOUR Scale in predicting mortality and functional outcomes. Five studies demonstrated equivalence between the FOUR Scales compared with the Glasgow Coma Score in predicting mortality and functional outcome. The FOUR Scale has been shown to be a good predictor of outcome in many patients with decreased level of consciousness. So this can provide an overview to nurses in assessing a good level of awareness and reliability.